Etruscan (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The present essay deals with the principal features of the Etruscan language in order to reconstruct a picture as updated and accurate as possible. Beginning with the state of the art in the Etruscan studies, we will discuss the methods of interpretation, the existing corpora, the number and tipology of the inscriptions, the phonetic, morphologic, typological and syntactic features, the lexicon, the writing and the onomastic system. In this essay we will also consider the still extant limits in our understanding of the Etruscan and the future challeges.
Keywords: Etruscan; Etruscan language; Morphology; Writing; Lexicon; Syntax